2011
DOI: 10.1007/s10530-011-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

History of exposure to herbivores increases the compensatory ability of an invasive plant

Abstract: Release from natural enemies is frequently cited as an important factor contributing to plant invasions. But such effects are likely to be temporary-native herbivores can form new plant-herbivore associations and co-evolved insects might reach the new range. While the potential effects of the initial enemy release have been well studied, the consequences of any resumption of herbivory are poorly understood. Alternanthera philoxeroides is one of the most widespread invasive plants in China and is attacked both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This would indicate that success of this highly invasive species in introduced areas is likely unaffected by release from enemies. In China, where Alternanthera philoxeroides is a prolific invader, impact of herbivory from a natural and newly associated enemy was tested to see if enemy release could explain its success (Lu & Ding, 2012). Results indicated that prior exposure to any type of herbivory allowed the plants to partially compensate for subsequent herbivory by accumulating greater root mass.…”
Section: Enemy Release and Evolution Of Increased Competitive Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This would indicate that success of this highly invasive species in introduced areas is likely unaffected by release from enemies. In China, where Alternanthera philoxeroides is a prolific invader, impact of herbivory from a natural and newly associated enemy was tested to see if enemy release could explain its success (Lu & Ding, 2012). Results indicated that prior exposure to any type of herbivory allowed the plants to partially compensate for subsequent herbivory by accumulating greater root mass.…”
Section: Enemy Release and Evolution Of Increased Competitive Abilitymentioning
confidence: 99%
“…Results indicated that prior exposure to any type of herbivory allowed the plants to partially compensate for subsequent herbivory by accumulating greater root mass. Lu & Ding (2012) suggest that enemy release may only be temporary with generalist herbivores forming new associations in the introduced environment, and should be a consideration in developing biocontrol strategies. In the north-eastern United States where the introduced water-chestnut, Trapa natans, is a problematic invader, researchers assessed if a native herbivorous beetle could limit its spread (Ding & Blossey, 2005).…”
Section: Enemy Release and Evolution Of Increased Competitive Abilitymentioning
confidence: 99%
“…). Host specificity and the potential for host shifts are important criteria for screening and post‐release evaluation of biological control agents for invasive plants (Ma ; van Klinken & Edwards ; Lu & Ding ).…”
Section: Introductionmentioning
confidence: 99%
“…), or overcompensation (Schierenbeck et al. , Lu and Ding ). These diverse findings suggest that tolerance may be idiosyncratic among invasive species; however, differing conclusions among single‐invader studies may also be attributable to differences in experimental design.…”
Section: Introductionmentioning
confidence: 99%